Two novel Brugada syndrome-associated mutations increase K(V)4.3 membrane expression and function - YOU, TAO (Int J Mol Med, 2015)
The human cardiac fast transient outward K(+) channel is composed of the K(V)4.3 α subunit encoded by KCND3 and the K(+) channel-interacting protein 2 (KChIP2) β subunit, and determines the early repolarization of the action potential (AP). Two human mutations (G600R and L450F) in K(V)4.3 are associated with Brugada syndrome and they increase the K(V)4.3/KChIP2-encoded fast transient outward K(+) current (I(to,f)) and cause the stable loss of the AP dome. However, the detailed mechanisms underlying the gain of I(to,f) function by these two mutations are largely unknown. The experiments in the present study were undertaken to investigate the effect of these mutations and the underlying mechanism. Whole cell patch-clamp recording was performed in HEK-293 cells expressing K(V)4.3-wild-type (WT) and K(V)4.3 mutants with KChIP2. The two individual mutant-encoded currents were significantly increased but the kinetics of the channels affected by the two mutations were different. The two mutations slowed K(V)4.3/KChIP2-encoded channel inactivation; they did not increase the recovery from the K(V)4.3/KChIP2-encoded channel inactivation. Western blotting showed that total K(V)4.3 protein was significantly augmented in HEK-293 cells expressing the two individual mutants with KChIP2. Furthermore, immunofluorescence confocal microscopy demonstrated that the K(V)4.3 channel protein was expressed more in the cell membrane compared to the cytoplasm in cells that expressed individual mutants with KChIP2. Also, KChIP2 increased the amount of channel protein in the cell membrane of K(V)4.3 mutants significantly more than K(V)4.3-WT. Reverse transcription-polymerase chain reaction showed that K(V)4.3 mRNA was not significantly changed by individual mutations in the presence of KChIP2. Taken together, the present study revealed that the mutations cause a gain-of-function of K(V)4.3/KChIP2-encoded channels by increasing membrane protein expression and slowing channel inactivation.